(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
The Effect of Segmenting, Targeting, and Positioning on Purchasing Decisions for Dewi Seri Coffee at CV Dewi Starindo. This study aims to determine how much influence segmenting, targeting, and positioning have on purchasing decisions for Dewi Seri coffee at CV Dewi Starindo. The sample in this study consisted of 100 respondents who were selected using the accidental sampling method. Data were collected using a questionnaire and analyzed using quantitative descriptive analysis and Structural Equation Model (SEM-PLS). The results show that segmenting, targeting, and positioning have a positive and significant effect on purchasing decisions for Dewi Seri Coffee at CV Dewi Starindo. In addition, the reliability analysis results show that the variables used in the study have a good level of reliability. The R2 square value in this study shows a value of 0.62, which means segmenting, targeting, and positioning have an influence of 62% on purchasing decisions. Suggestions that can be given to companies by improving the taste and shape of different products for Dewi Seri Coffee and increasing promotional media using social media to determine market segments more freely. This research provides important implications for companies to consider the influence of segmenting, targeting, and positioning in improving purchasing decisions for Dewi Seri Coffee.